(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
This study investigated the effectiveness of using sketchnoting as a pedagogical tool in the delivery of Printed Modular Distance Learning to Grade 12 students. The study employed a mixed-method research design, with 68 students selected through matched pairing of characteristics and divided into a treatment group and a comparison group. The treatment group received sketchnoting activities, while the comparison group did not. The study measured the effectiveness of the intervention through posttests of the treatment and comparison groups and a post-exposure self-report survey to understand the learning benefits and experiences of the students who were exposed to sketchnoting activities. The results of the study showed that the use of sketchnoting had a statistically and practically significant impact on the study of General Chemistry lessons. The utilization of sketchnoting significantly improved the students’ test scores. The students also reported positive experiences and appreciated the learning benefits of using sketchnoting, although there were a few demotivating experiences. The findings of this study support the use of sketchnoting as an effective pedagogical tool in Printed Modular Distance Learning.